Triplex systems: Accelerated and outdoor tests - Seré, Pablo Ricardo (2018)
The protective paint/galvanized steel system is called duplex and it is claimed that protects steel from corrosion synergistically. The triplex system adds a pretreatment between the paint and the substrate in order to enhance the corrosion protection or paint adhesion. In this work, the behavior against the corrosion of electrogalvanized steel pretreated with a commercial silane, mercaptopropyltrimethoxysilane (MTMO) or a chromium(III)-based solution (Cr) was studied. Pretreated samples were painted with an alkyd system and exposed in humidity, prohesion chambers or xenon lamp artificial weathering. Besides, some of them were exposed in outdoor experimental station (Posadas, Misiones Province, Argentina, 27° 22′S and 55° 53′W) for 5 years. The evolution of the different triplex systems was evaluated by visual observation, loss of gloss, color variation, loss of adhesion, and electrochemical impedance spectroscopy. A painted sample without pretreatment was used as control. Subjected to accelerated tests, the highest protective efficiency was obtained in samples pretreated with MTMO or Cr. However, in the outdoor tests the best behavior corresponds to the control samples because the pretreated ones failed due to adhesion problems.